MEASUREMENT OF BRAND ATTITUDE IN IMPROVING CONSUMER LOYALTY IN NIAR CHIPS BUSINESS IN BONE DISTRICT - Elysa Natalia; Agus Syam; Asmayanti; Muhammad Rakib; Andika Isma (Jurnal Salome : Multidisipliner Keilmuan, 2025)
Brand attitude becomes one of the important factors in understanding consumer perception and loyalty towards a brand.  In the midst of increasingly fierce competition, measuring brand attitude has become one of the keys to understanding consumer attitudes towards a brand or brand attitude. This research aims to develop an effective brand attitude measurement model to enhance consumer loyalty for Keripik Niar.  This research uses the research and development (R&D) method with the 4D model, which consists of four stages: define, design, develop, and disseminate.  Data collection activities were carried out through observation, interviews, and documentation.  The data analysis technique uses qualitative descriptive analysis techniques.  The research results show that the brand attitude measurement model using the 4D model approach is effective in depicting consumer attitudes towards Keripik Niar through four indicators: brand trust, brand love, brand reliability, and purchase tendency due to the brand.  This model helps business owners understand consumer needs and expectations, thereby enhancing brand image and consumer loyalty.